Imaging Analysis of Patients With Meniere's Disease Treated With Endolymphatic Sac-Mastoid Shunt Surgery - Li, Yawei; Lv, Yafeng; Hu, Na; Li, Xiaofei; Wang, Haibo; Zhang, Daogong (Frontiers in Surgery, 2022)
Objective: Endolymphatic sac surgery is effective in treating intractable Meniere's disease (MD), but the underlying mechanism is still unknown. Our study investigated the mechanism by which endolymphatic sac-mastoid shunt (EMS) surgery is effective in treating MD by means of imaging. Methods: The experiment included 19 patients with intractable MD who underwent 3D-fluid-attenuated inversion recovery (FLAIR) MRI with a 3-Tesla unit 6 h after intravenous administration of gadolinium, before EMS, and 2 years after the surgery. The enhanced perilymphatic space in the bilateral cochlea, vestibule, and canals was visualized and compared with that in the endolymphatic space by quantitatively scoring the scala vestibuli of the cochlea and by measuring the developing area of the vestibules quantitatively. Results: Gadolinium was present in the perilymph of the inner ear in the cochlea, vestibules, and canals of all patients. At the 2-year follow-up, 14 (73.68%) patients had vertigo control. Both before and 2 years after surgery, significant differences were observed in the scala vestibuli scores and the area of vestibular perilymph between the affected and healthy sides. The scala vestibuli scores and the area of vestibular perilymph, however, did not differ when comparing them before and after surgery. Conclusions: According to our results, endolymphatic hydrops was not significantly reduced by surgery. The mechanism by which EMS controls vertigo might be unrelated to the improvement in hydrops.